2020
DOI: 10.1177/0018578720925388
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Verapamil Versus Diltiazem Continuous Infusion for Acute Rate Control of Atrial Fibrillation at an Academic Medical Center

Abstract: Purpose: Due to critical shortages of intravenous diltiazem in 2018, the Ohio State University Wexner Medical Center (OSUWMC) adopted intravenous verapamil as an alternative. However, there is a paucity of data supporting the use of intravenous verapamil infusions for rate control in the acute treatment of atrial arrhythmias. The purpose of this study was to determine the safety and efficacy of intravenous verapamil as compared with diltiazem for the acute treatment of atrial arrhythmias. Methods: This retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Specifically, diltiazem is associated with less interactions with cardiac glycosides and beta-blockers, has less negative inotropic effects, and has less conduction disturbances. 35,36 Verapamil has also been shown to decrease gut motility and cause constipation due to its increased effect on smooth muscle relative to diltiazem. 37 In addition, in data for atrial fibrillation, verapamil was shown to increase the risk of symptomatic hypotension including cases of life-threatening hypotension.…”
Section: Pharmacologic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, diltiazem is associated with less interactions with cardiac glycosides and beta-blockers, has less negative inotropic effects, and has less conduction disturbances. 35,36 Verapamil has also been shown to decrease gut motility and cause constipation due to its increased effect on smooth muscle relative to diltiazem. 37 In addition, in data for atrial fibrillation, verapamil was shown to increase the risk of symptomatic hypotension including cases of life-threatening hypotension.…”
Section: Pharmacologic Therapymentioning
confidence: 99%
“…37 In addition, in data for atrial fibrillation, verapamil was shown to increase the risk of symptomatic hypotension including cases of life-threatening hypotension. 36 For these reasons, it may be reasonable to choose diltiazem over verapamil in patients presenting in SVT despite the limited amount of comparative data. If institutions choose to routinely use non-DHP CCB for the treatment of PSVT, these agents should be added to automated dispensing cabinets in the ED to facilitate rapid delivery to the patient.…”
Section: Pharmacologic Therapymentioning
confidence: 99%
“…Only 4% in the diltiazem group and 1.4% in the verapamil group required the addition of amiodarone infusion on top of non-dihydropyridine CCBs in order to achieve a heart rate less than 100 bpm. There was no significant difference between the two treatment groups regarding the need for inotropes/vasopressors and the incidence of hypotension (defined as systolic blood pressure < 90 mmHg) or bradycardia [49]. Likewise, a study of 182 patients with AF or atrial flutter, 10% of whom had LVEF < 50%, demonstrated that the safety and efficacy outcomes were similar for verapamil and diltiazem when used for acute rate control [50].…”
Section: Rate Controlmentioning
confidence: 99%
“…Intra-arterial (i.a.) verapamil is a safe and routine practice to treat cerebral vasospasm, and is less likely to lower perfusion pressure (Forshay et al, 2021) which is detrimental for the ischemic tissue in a stroke brain. The study by Bix and others (2017) has recently shown that the selective i.a.…”
Section: Introductionmentioning
confidence: 99%